2018
DOI: 10.2147/copd.s178951
|View full text |Cite
|
Sign up to set email alerts
|

A comparative analysis of errors in inhaler technique among COPD versus asthma patients

Abstract: PurposeThis study was designed to evaluate errors in inhaler technique in COPD vs asthma patients and to investigate the association of poor inhaler technique with patient demographics and clinical variables.Patients and methodsA total of 509 adult patients with COPD (n=328) or asthma (n=181) who were currently using an inhaler device were included in this study. Data on patient demographics, duration of disease, type and duration of inhaler therapy, and assessment of inhaler technique were recorded.ResultsMet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

8
33
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(41 citation statements)
references
References 33 publications
8
33
0
Order By: Relevance
“…e ndings of this study showed that there was an e ective improvement in the quality of life in both the groups (test and is in concordance with the nding of Ocakli et al [22] which also stated that most selected form of inhaler therapy was metered dose inhaler than dry powder inhaler. e reason behind more users of MDI as compared to DPI might be it is cheaper and convenient to use than DPI in developing countries like Nepal.…”
Section: Discussionsupporting
confidence: 91%
“…e ndings of this study showed that there was an e ective improvement in the quality of life in both the groups (test and is in concordance with the nding of Ocakli et al [22] which also stated that most selected form of inhaler therapy was metered dose inhaler than dry powder inhaler. e reason behind more users of MDI as compared to DPI might be it is cheaper and convenient to use than DPI in developing countries like Nepal.…”
Section: Discussionsupporting
confidence: 91%
“…Many types of devices are available for the delivery of inhaled drugs [8]; however, studies have shown that * 32-89% of patients do not use their inhaler correctly [9][10][11][12][13][14]. A similar rate of inhaler technique errors occurs for patients with asthma or COPD [15]. Correct inhaler technique is important because inhaler misuse is associated with insufficient disease control and poor patient outcomes [16], such as an increased risk of hospitalization due to an asthma exacerbation.…”
Section: Introductionmentioning
confidence: 99%
“…In this survey, despite the involvement of all the responders, none of them were able to perform all steps of the MDI technique correctly, which will be reflected in the patients that will not have adequate instruction. It is also well known that only 8-20% of the drug reaches bronchial airways when MDI is used correctly, thus when the MDI technique is not properly applied, the amount of drug delivered into the lungs is lower than it should be producing worse disease outcomes [4,[29][30][31]. Therefore, for the proper administration of drugs using MDI, each one of the different steps of the MDI technique must be performed correctly.…”
Section: Discussionmentioning
confidence: 99%
“…Concerning technique, specific steps and good coordination are necessary for the proper use of this device. A less than optimal technique is commonly observed in respiratory patients and can result in decreased drug delivery and potentially reducing efficacy [4].…”
Section: Introductionmentioning
confidence: 99%